CONSUMER BANKRUPTCY WITH A CROSS-BORDER ELEMENT IDEA, NORMS AND SOME DOUBTS - Bodul, Dejan (EU and comparative law issues and challenges series (ECLIC), 2018)
The tendency towards a harmonisation of procedural law in the European Union is increasingly stronger and gaining importance. It is achieved by reaching a consensus in overcoming differences between legal systems. The European Union is at present an alliance of 28 sovereign states aimed at establishing an area of freedom, security and justice. Moreover, that the European Union is a creation in statu nascendi is clearly visible in the current situation and the development trends of legal harmonisation in the field of international consumer insolvency law. Consumers are frequently travelling, buying abroad and entering into contracts with foreign credit institutions. As they move from one country to another and are employed in countries other than the one in which they reside, insolvency and debt relief at the cross-border/international level is becoming more widespread, and more effective regulation is a necessity. The aim of this paper is to point out potential problems in the regulation of consumer bankruptcy with a cross-border element that may occur in the case-law of the Croatian courts. In the analysis of the institute of consumer bankruptcy with a cross-border element through the solutions of the Regulation 1346/2000 and Regulation 2015/848 (recast) we used a methodological procedure which involves the study of domestic and foreign literature, relevant legal provisions, as well as an analysis of domestic and foreign legal practices. We consider it important to note that the framework of this paper does not allow a detailed analysis and that we are forced to limit ourselves exclusively to some aspects of the issue at hand.